A study on mast cell variation in neoplastic and non neoplastic disease of uterine cervix - Mainali, N; Sihna, AK; Upadhyaya, P; Upreti, D (Journal of Pathology of Nepal, 2014)
Background: Mast cells are heterogeneous group of immune cells involved in multiple biological events. The significance of mast cells in uterine tumor surveillance has been studied with conflicting results. The presence of mast cell in tumor has been described as evidence of a host immunologic anti tumor response and if they are abundant the prognosis is good. However in other studies, with the help of different granules of mast cell, it is said to be very closely related with angiogenesis and tumor invasion. The study aims to analyze the histomorphologic changes with special reference to mast cells in different neoplastic and non neoplastic disease of uterine cervix, and also the relationship of the mast cell population with degree of anaplasia and mitotic figures. Materials and methods: Cervical biopsies received in the department of Pathology for HPE were stained with H& E stain and toludine blue for the identification of mast cell Result: Out of a total of 100 cases, 82 were non neoplastic cases with the mean mast cell count of 83.73 and mean age of patient being 44.30 year. Eighteen neoplastic cases were included which had mean mast cell count of 13.5 and mean age of 49.5 year. Conclusion: Mast cell was found to be highest in non Neoplastic lesion with increase count in polypoidal cervicitis. There was a statistical significance variation between mast cell count in neoplastic and non Neoplastic disease of the cervix. However,role of age in mast cell count was least significant. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11594 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 658-662